2014
DOI: 10.12688/f1000research.2026.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of phenothrin mousse, phenothrin lotion, and wet-combing for treatment of head louse infestation in the UK: a pragmatic randomised, controlled, assessor blind trial

Abstract: In this investigation of effectiveness of an alternative pediculicide dosage form, we recruited 228 children and 50 adult participants from Bedfordshire, UK, to a randomised, controlled, assessor blind trial comparing two insecticide products with mechanical removal of lice as a control group.  Participants using insecticide were treated with either the investigative 0.5% phenothrin mousse, for 30 minutes, or 0.2% phenothrin lotion, for 2 hours as the reference product.  Both treatments were applied only once,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…Interestingly, contradictory results were obtained in a study that showed that wet combing (bug buster kit) was significantly better than pediculicides (pyrethroid or organophosphate) [23]. However, the comparison with the United Kingdom is not appropriate, because it has been reported that head lice in the UK are resistant to pyrethroids such as permethrin [24].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, contradictory results were obtained in a study that showed that wet combing (bug buster kit) was significantly better than pediculicides (pyrethroid or organophosphate) [23]. However, the comparison with the United Kingdom is not appropriate, because it has been reported that head lice in the UK are resistant to pyrethroids such as permethrin [24].…”
Section: Discussionmentioning
confidence: 99%
“… Phenothrin 0.2% lotion on dry hair, wash out after 2 h {level of evidence Ib; grade A recommendation} Malathion 0.5% lotion on dry hair, wash out 12 h after application (level of evidence IV; grade C recommendation).…”
Section: Second‐line Therapymentioning
confidence: 99%
“…As with permethrin, resistance to this compound has already appeared in France [ 109 ], UK [ 110 ], and the Czech Republic [ 111 ]. In clinical trials, phenothrin has been demonstrated to also be more effective than wet-combing [ 21 ]. It seems likely that resistance to pyrethroids will develop much more rapidly than was the case with older compounds [ 112 ].…”
Section: Treatment Strategiesmentioning
confidence: 99%